Impact of maternal late gestation undernutrition on surfactant maturation, pulmonary blood flow and oxygen delivery measured by magnetic resonance imaging in the sheep fetus. (22nd September 2021) - Ren, Jiaqi; Darby, Jack R. T.; Lock, Mitchell C.; Holman, Stacey L.; Saini, Brahmdeep S.; Bradshaw, Emma L.; Orgeig, Sandra; Perumal, Sunthara R.; Wiese, Michael D.; Macgowan, Christopher K.; Seed, Mike; Morrison, Janna L.
Abstract : Abstract: Restriction of fetal substrate supply has an adverse effect on surfactant maturation in the lung and thus affects the transition from in utero placental oxygenation to pulmonary ventilation ex utero . The effects on surfactant maturation are mediated by alteration in mechanisms regulating surfactant protein and phospholipid synthesis. This study aimed to determine the effects of late gestation maternal undernutrition (LGUN) and LGUN plus fetal glucose infusion (LGUN+G) compared to Control on surfactant maturation and lung development, and the relationship with pulmonary blood flow and oxygen delivery ( D O 2 ) measured by magnetic resonance imaging (MRI) with molecules that regulate lung development. LGUN from 115 to 140 days' gestation significantly decreased fetal body weight, which was normalized by glucose infusion. LGUN and LGUN+G resulted in decreased fetal plasma glucose concentration, with no change in fetal arterial P O 2 compared to control. There was no effect of LGUN and LGUN+G on the mRNA expression of surfactant proteins ( SFTP ) and genes regulating surfactant maturation in the fetal lung. However, blood flow in the main pulmonary artery was significantly increased in LGUN, despite no change in blood flow in the left or right pulmonary artery and D O 2 to the fetal lung. There was a negative relationship between left pulmonary artery flow and D O 2 to the left lung with SFTP‐B and GLUT1 mRNA expression, while their relationship with VEGFR2 was positive. These results suggest that increased pulmonary blood flow measured by MRI may have an adverse effect on surfactant maturation during fetal lung development. Key points: Maternal undernutrition during gestation alters fetal lung development by impacting surfactant maturation. However, the direction of change remains controversial. We examined the effects of maternal late gestation maternal undernutrition (LGUN) on maternal and fetal outcomes, signalling pathways involved in fetal lung development, pulmonary haemodynamics and oxygen delivery in sheep using a combination of molecular and magnetic resonance imaging (MRI) techniques. LGUN decreased fetal plasma glucose concentration without affecting arterial P O 2 . Surfactant maturation was not affected; however, main pulmonary artery blood flow was significantly increased in the LGUN fetuses. This is the first study to explore the relationship between in utero MRI measures of pulmonary haemodynamics and lung development. Across all treatment groups, left pulmonary artery blood flow and oxygen delivery were negatively correlated with surfactant protein B mRNA and protein expression in late gestation. Abstract : Abstract figure legend The effects of maternal undernutrition in late gestation on fetal lung development.